2020
DOI: 10.1093/dote/doaa064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and concordant occurrence of esophageal, gastric, duodenal, and colonic eosinophilia

Abstract: Summary Eosinophilic esophagitis, gastritis, duodenitis, and colitis are rare diseases. Few studies have been able to accumulate sufficiently large number of patients to analyze their clinical epidemiology. The aim of the present epidemiologic study was to examine the prevalence and concordant occurrence of gastrointestinal (GI) eosinophilia. Using a database of histopathologic records, a cross-sectional study among 302,061 patients undergoing bidirectional endoscopy evaluated the concordant occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Of the 50 studies with documentation of demographic distribution of age, race, ethnicity, sex, gender, BMI, rural versus urban residence, or insurance status, 12 provided data to support comparison of the demographic distribution of individuals with an EGID to that of the underlying source population ( Table II ). 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Six of these studies were conducted using pathology databases, 2 were conducted using claims data, 3 were conducted using electronic health record (EHR) data sources, and 1 was conducted from a population-based online survey. All but 2 studies were conducted in populations in the United States, with one study using pathology data from New Zealand 35 and another study using EHRs from Spain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 50 studies with documentation of demographic distribution of age, race, ethnicity, sex, gender, BMI, rural versus urban residence, or insurance status, 12 provided data to support comparison of the demographic distribution of individuals with an EGID to that of the underlying source population ( Table II ). 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Six of these studies were conducted using pathology databases, 2 were conducted using claims data, 3 were conducted using electronic health record (EHR) data sources, and 1 was conducted from a population-based online survey. All but 2 studies were conducted in populations in the United States, with one study using pathology data from New Zealand 35 and another study using EHRs from Spain.…”
Section: Resultsmentioning
confidence: 99%
“…For the nonesophageal EGIDs, 2 studies provided sex or gender distribution data for both the EGID type examined and the source population. 33 , 38 Eosinophilic gastritis or gastric eosinophilia, eosinophilic gastroenteritis or duodenal eosinophilia, or eosinophilic colitis or colonic eosinophilia were examined, and with the exception of the Jensen et al 33 study (n = 11,569,217 in the source population), which reported a somewhat lower proportion of male patients for eosinophilic gastritis relative to the source population (38.6% vs 47.9%; P = .004), no significant differences were observed for sex or gender distribution ( Table II ).…”
Section: Resultsmentioning
confidence: 99%
“…La duodenitis eosinofílica aislada tiene una prevalencia de 0,03 por cada 1000 registros de endoscopia bidireccional (12) . Se conoce poco sobre su fisiopatología, pero se considera que la respuesta CD4/Th2 ya sea mediada o no por IgE, así como las citoquinas y quimioquinas responsables del reclutamiento de eosinófilos entre ellas IL13, IL5 juegan un papel importante, la infiltración de eosinófilos en tejido y su degranulación lleva a fibrosis tisular, trombosis, vasculitis de pequeños vasos e inflamación persistente.…”
Section: Discussionunclassified
“…esophageal eosinophils; the eosinophil level is highest in the ascending colon, tapers to lower levels in the recto-sigmoid colon, 20,21 and increases during inflammation in many conditions. 16 As eosinophil-rich inflammation is not exclusive to EoC, primary EoC is a diagnosis that can be made only after all other known causes for increased colonic mucosal eosinophils have been eliminated.…”
Section: Impactmentioning
confidence: 99%